PENGARUH RAGAM PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS PADA KONSUMEN TOKO MANTAN KARYAWAN DI KOTA BENGKULU) - Dika Febriani; Sri Ekowati (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2022)
This study aims to determine the effect of product variety and service quality on purchasing decisions (a case study on Mantan Karyawan store consumers in Bengkulu City). This research is a quantitative descriptive study. The object of this research is consumer at Mantan Karyawan store located in Bengkulu City. Sampling was done by accidental sampling technique. The number of respondents in this study was 140 consumers. The data of the study was collected by using questionnaires. The collected data was then analyzed by using multiple linear regression analysis and hypothesis testing, t-tes and F-tes. The results of the study show that variables, product variety and service quality had a positive and significant effect on purchasing decisions at Mantan Karyawan stores. Partially the two variables, product variety and service quality have a positive and significant influence on purchasing decision. The more variety of products available in the store, the better the quality of service provided in accordance with the wishes of consumers, then the purchase decision will increase.Keywords: Product Variety, Service Quality, Purchase DecisionÂ